Fenofibrate enhances barrier function of endothelial continuum within the metastatic niche of prostate cancer cells. (February 2015) - Piwowarczyk, Katarzyna; Wybieralska, Ewa; Baran, Jarosław; Borowczyk, Julia; Rybak, Paulina; Kosińska, Milena; Włodarczyk, Anna Julia; Michalik, Marta; Siedlar, Maciej; Madeja, Zbigniew; Dobrucki, Jerzy; Reiss, Krzysztof; et al.
<x xml:space="preserve">Abstract</x> Objective: Extravasation of circulating cancer cells is an important step of the metastatic cascade and a potential target for anti-cancer strategies based on vasoprotective drugs. Reports on anti-cancer effects of fenofibrate (FF) prompted us to analyze its influence on the endothelial barrier function during prostate cancer cell diapedesis. Research design and methods: In vitro co-cultures of endothelial cells with cancer cells imitate the 'metastatic niche' in vivo. We qualitatively and quantitatively estimated the effect of 25 μM FF on the events which accompany prostate carcinoma cell diapedesis, with the special emphasis on endothelial cell mobilization. Results: Fenofibrate attenuated cancer cell diapedesis via augmenting endothelial cell adhesion to the substratum rather than through the effect on intercellular communication networks within the metastatic niche. The inhibition of endothelial cell motility was accompanied by the activation of PPARα-dependent and PPARα-independent reactive oxygen species signaling, Akt and focal adhesion kinase (FAK) phosphorylation, in the absence of cytotoxic effects in endothelial cells. Conclusions: Fenofibrate reduces endothelial cell susceptibility to the paracrine signals received from prostate carcinoma cells, thus inhibiting endothelial cell mobilization and reducing paracellular permeability of endothelium in the metastatic niche. Our data provide a mechanistic rationale for extending the clinical use of FF and for the combination of this well tolerated vasoactive drug with the existing multidrug regimens used in prostate cancer therapy.